A context‐aware and intelligent framework for the secure mission critical systems. Issue 6 (12th April 2020) - Sikandar, Usman; Taha, Muhammad; Sarwar, Sohail; Safyan, M.; Qayyum, Zia Ul; Ali, Amjad; Iqbal, Muddesar
Abstract: Recent technological advancements in pervasive systems have shown the potential to address challenges in the military domain. Research developments in military‐based mission‐critical systems have refined a lot as in autopilot, sensing true target behavior, battle damage conditions, acquiring, and manipulating command control information. However, the application of pervasive systems in the military domain is still evolving. In this paper, an intelligent framework has been proposed for mission‐critical systems to incorporate advanced heterogeneous communication protocols; service‐oriented layered structure and context‐aware information manipulation. The proposed framework addresses the limitation of "time‐space" constraints in mission‐critical systems that have been improved significantly. This improvement is courtesy to enhancing situation‐aware tactical capabilities such as localization, decision significance, strategic span, strategic intentions, resource coordination, and profiling concerning the situation. A comprehensive use case model has been presented for a typical battle‐field scenario followed by a comparison of the proposed framework with existing techniques. It is evident from experiments and analyses that the proposed framework provides more effective and seamless interaction with contextual resources to improve tactical capabilities.